Infant and young child feeding practice among mothers with 0–24 months old children in Slum areas of Bahir Dar City, Ethiopia - Demilew, Yeshalem Mulugeta (Int Breastfeed J, 2017)
BACKGROUND: Adequate nutrition during infancy and early childhood is essential to ensure the health, growth and development of children. However, infant feeding practice is suboptimal in Bahir Dar City, Ethiopia. The slum area is a heavily populated urban informal settlement characterized by substandard housing, squalor, with a lack of reliable sanitation services, supply of clean water, reliable electricity, law enforcement and other basic services. Residents of the slum area were poor and less educated. This further compromises infant feeding practice. The aim of this study was to assess infant and young child feeding practice among mothers with 0–24 month old children in the study area. METHODS: A community based cross-sectional study was conducted among 423 mothers with 0–24 month old children from June 01-30 / 2016. Simple random sampling technique was used to select the respondents. Infant and young child feeding practice was assessed using the fifteen World Health Organisation (WHO) criteria. RESULTS: The prevalence of exclusive breastfeeding practice was 113 (84%). Sixty (15%) mothers gave prelacteal feeds and, 96 (23%) mothers used a bottle to feed their index child. Appropriate complementary feeding practice was only 20 (7%). Thirty nine out of forty mothers introduced complementary food timely, 131 (47%) of mothers gave the minimum meal frequency, and 20 (7%) children took the minimum food diversity and acceptable diet. Independent predictors for complementary feeding practice were having secondary and above education of the mother, receiving postnatal care, possession of radio and giving birth at hospital. CONCLUSION: In this study infant and young child feeding (IYCF) practice was poor. Therefore, there is a need for strengthening the promotion on IYCF practice during postnatal care and using mass media to giving﻿ emphasis for ﻿optimal complementary feeding practices, especially for mothers with a lower educational status.